Association between c-type lectin-like receptor 2 and microsatellite instability in colorectal cancer: a cross-sectional study - Xin Zhang; Jia-rui Yuan; Xin Wang; Shuang Fu; Rui-tao Wang; Guang-yu Wang (BMC Cancer, 2022)
Abstract Background As a transmembrane protein, C-type lectin-like receptor 2 (CLEC-2) is mainly expressed on platelets and released into plasma after platelet activation. Activated platelets participate in the regulation of innate immune cells. Patients with different microsatellite statuses have distinct immune profiles. This study aimed to investigate the association of plasma CLEC-2 levels with microsatellite status among colorectal cancer (CRC) patients. Methods A cross-sectional analysis of 430 CRC patients from Harbin Medical University Cancer Hospital was conducted. CLEC-2 levels were measured with fasting venous blood samples drawn from each participant before any treatment. The microsatellite status was evaluated with DNA obtained from fresh frozen tumor tissue samples. The other clinical data were collected and recorded based on the medical system records. Results CLEC-2 levels were significantly higher among patients with high microsatellite instability phenotype than the stable microsatellite group, adjusting for other confounding variables. Conclusions The increased CLEC-2 is associated with the high microsatellite instability subtype of CRC.